Epidemiology: Analysis And Construction Of A Mathematical And Computational Model In Complex Systems For The COVID-19 Pandemic - Pinto, Luan Crisostomo; Defante, Maria Luiza Rodrigues; Silva, Rodrigo Lacerda da (Anais do Encontro Nacional de Computação dos Institutos Federais (ENCompIF); 2023: Anais do X Encontro Nacional de Computação dos Institutos FederaisDO - 10.5753/encompif.2023.229932, 2023)
The textbook mathematical model in epidemiology - SIS (Susceptible-Infected-Susceptible) provided the basis for proposing a new and improved model based on the observable behaviors of the current Covid-19 pandemic. The goal of this study was to analyze the behavior of the system and the influence of the LockDown factor on infected individuals. The model proposed here, called SIERDASHQ (Susceptible - Infected - Exposed - Recovered - Deceased - Asymptomatic - Symptomatic - Hospitalized - Quarantined), was simulated with values that expressed the situation of the pandemic at the national level, making it possible to compare data to the graphics produced by the program, which confirms the validity of the model.